2014
DOI: 10.1039/c4ay01522c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high sensitivity photometric procedure for the determination of vanadium in mineral and fresh waters employing a downsized multicommuted flow analysis approach

Abstract: This article focuses on the development of an analytical procedure for the photometric determination of vanadium in fresh and mineral waters, implemented employing a downsized multicommuted flow analysis approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(93 reference statements)
0
5
0
2
Order By: Relevance
“…Usually, when a LED is used as the radiation source in photometric detection, the absorbance is calculated considering the dark measurement. 33,34 Earlier work using a flow cell with geometry identical to that used in the current work, demonstrated that better adherence to the Beer–Lambert–Bouguer low was achieved by replacing the dark measurement by the residual measurement related to the diffuse radiation, 27 which was done using the equation shown below. where Abs = absorbance, Fs = full scale signal (mV) generated by the photodetector maintaining the flow cell filled with carrier fluid, Si = signal (mV) generated by the photodetector maintaining the flow cell filled with a light-absorbing compound, and Sm = residual measurement (mV), k = constant, c = analyte concentration, and x = optical length of flow cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, when a LED is used as the radiation source in photometric detection, the absorbance is calculated considering the dark measurement. 33,34 Earlier work using a flow cell with geometry identical to that used in the current work, demonstrated that better adherence to the Beer–Lambert–Bouguer low was achieved by replacing the dark measurement by the residual measurement related to the diffuse radiation, 27 which was done using the equation shown below. where Abs = absorbance, Fs = full scale signal (mV) generated by the photodetector maintaining the flow cell filled with carrier fluid, Si = signal (mV) generated by the photodetector maintaining the flow cell filled with a light-absorbing compound, and Sm = residual measurement (mV), k = constant, c = analyte concentration, and x = optical length of flow cell.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, when a LED is used as the radiation source in photometric detection, the absorbance is calculated considering the dark measurement. 33,34 Earlier work using a flow cell with geometry identical to that used in the current work, demonstrated that better adherence to the Beer-Lambert-Bouguer low was achieved by replacing the dark measurement by the residual measurement related to the diffuse radiation, 27 which was done using the equation shown below.…”
Section: General Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalmente, quando o LED é usado como fonte de radiação na detecção fotométrica, a absorbância é calculada considerando a medição no escuro. 74,77,78 Trabalhos recentes, usando uma cela de fluxo com geometria idêntica à utilizada no presente trabalho, demonstraram que há uma melhor adequação à lei BouguerLambert-Beer quando o sinal da leitura no escuro é substituído pela leitura da …”
Section: Descrição Do Fotômetrounclassified
“…Esta leitura tem sido chamada de sinal residual e foi salva pelo software e usado para calcular a absorbância. 77,78 No modulo proposto, a amostra é inserida para encher o percurso analítico e a cela de fluxo, acionado as válvulas solenoide V 1 e V 4 e a mini-bomba peristáltica A reação tem inicio ao inserir as alíquotas das soluções de hidróxido de sódio e de ditizona no percurso analítico, acionando as válvulas V 2 , V 3 e V 4 em conjunto com a mini-bomba peristáltica Pp 1 . A reação é rápida, portanto não é necessário estabelecer um tempo de repouso para seu desenvolvimento.…”
Section: Amostrasunclassified